2023
DOI: 10.3390/ijerph20043639
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Multimorbidity, Inappropriate Medication and Adverse Outcomes of Inpatient Care: MoPIM Cohort Study

Abstract: There is no published evidence on the possible differences in multimorbidity, inappropriate prescribing, and adverse outcomes of care, simultaneously, from a sex perspective in older patients. We aimed to identify those possible differences in patients hospitalized because of a chronic disease exacerbation. A multicenter, prospective cohort study of 740 older hospitalized patients (≥65 years) was designed, registering sociodemographic variables, frailty, Barthel index, chronic conditions (CCs), geriatric syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In terms of the most common types of PIM category used, our findings are consistent with those of other studies in that the majority of the elderly patients in this study used potentially inappropriate cardiovascular medications, which were substantially more frequently taken by women than by men. Furthermore, the results of our analysis that women have higher use of a potentially inappropriate prescription is in line with some earlier research that reported a higher prevalence in women compared to men [ 6 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In terms of the most common types of PIM category used, our findings are consistent with those of other studies in that the majority of the elderly patients in this study used potentially inappropriate cardiovascular medications, which were substantially more frequently taken by women than by men. Furthermore, the results of our analysis that women have higher use of a potentially inappropriate prescription is in line with some earlier research that reported a higher prevalence in women compared to men [ 6 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, growing attention and consideration has been given to individual characteristics, including gender differences, in the context of medication use. Gender is a pivotal element in various aspects of healthcare, including the prevalence of chronic illness, healthcare utilization, medication utilization, adherence to medications, use of self-medication, and health outcomes [ 3 , 4 , 5 , 6 ]. In addition, gender differences are known to be driven by biological factors such as metabolism and hormones, which may impact the pharmacokinetics and pharmacodynamics of medications and health-related behavioral risk factors such as lifestyle and healthcare provider communication [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations